Komunikasi Kebijakan Publik Pemerintah dalam Mengumumkan Kenaikan Gaji Guru ASN dan Non ASN 2025 - Nurul Baridah Fauzi; Mayra Khalidazia Ahyar; Khairatun Hisan; Sayyidatina Vista Kintani; Nabila Nursabrina Daud; Winda Dwi Astuti Zebua (Kajian Administrasi Publik dan ilmu Komunikasi, 2025)
This study aims to analyze the government's communication strategy in communicating the salary increase policy for State Civil Apparatus (ASN) and non-ASN teachers in 2025. The study used a qualitative approach using a literature review method, examining various official government sources, policy reports, and relevant scientific publications. The analysis focused on three main aspects of the communication strategy: information transmission, message clarity, and consistency of communication between institutions. The results show that the government has utilized various communication channels, both conventional and digital, to disseminate the policy to the public. However, several obstacles remain, such as limited access to information in remote areas, the emergence of misinformation on social media, and suboptimal communication coordination between relevant institutions. On the other hand, the development of digital technology and the increasing transparency of public information provide significant opportunities to strengthen the effectiveness of policy communication. A more integrated, clear, and inclusive communication strategy is considered crucial for increasing public understanding and support for the teacher salary increase policy. This policy is expected to not only improve teacher welfare but also contribute to the sustainable improvement of the quality of national education.